Analysis of Halal Product Knowledge, Social Media Marketing, and Fear of Missing Out (FOMO) on Purchasing Decisions for Muslim Food Products in Binjai City - Zulfita, Elsa; Harmain, Hendra; Aisyah, Siti (JESI (Jurnal Ekonomi Syariah Indonesia), 2024)
This research explains how knowledge about halal products, web-based entertainment shows, and concerns about big opportunities (FOMO) influence students' purchasing choices in Binjai City. This research aims to determine the impact of information about halal goods, virtual entertainment shows, and concerns about missing out on big opportunities (FOMO) on students' purchasing choices. Meanwhile, questionnaires were given to 97 sample students. Based on the findings of data analysis, there is an influence on students' purchasing decisions in Binjai City on knowledge of halal products, social media marketing, and Fear of Missing Out (FOMO). The method of carrying out this exploration uses a quantitative methodology where this examination collects, displays, presents, and breaks down information quantitatively. This research uses primary data. The exploratory instrument used was a survey. Meanwhile, information-checking procedures include various relapse checks and t-count searches. The results of the research state that the information obtained, X1 has a specified count (3.201) > ttable (1.98580) and a Sig value <0.05 (0.02), so X2 has a significant effect if the value of tcount (4,980) is greater than t table (1,98580) and the value of sig is less than 0.05 (0.00), and X3 has a significant effect if the tcount value (2,833) is greater than t table (1.98580) and the Sig value is less than 0.05 (0.01). There is an opinion that the information reported regarding halal products, web-based entertainment promotions, and anxiety about missing out on big opportunities (FOMO) in the purchasing choices of students in Binjai City.